Postpartum ovulation and early pregnancy in the menstruating spiny mouse, Acomys cahirinus - Jarrod McKenna (Nature Portfolio, 2021)
Abstract Egyptian spiny mice are the only known species to have human-like menstruation and a postpartum ovulation. Unfortunately, no endocrine or morphological evidence has been provided for a postpartum ovulation in spiny mice, and while later stages of pregnancy have been well studied, early events including embryo implantation and spiral artery remodelling have not been reported. This study compared the sex steroid endocrinology and reproductive tract morphology of dams at eight timepoints (n = 40) postpartum to determine the timing of ovulation and the timing and invasiveness of embryo implantation in A. cahirinus. Reproductive tracts were fixed and stained for histology and immunohistochemistry, and plasma was prepared for enzyme-linked immunosorbent assay. Ovarian histology and estradiol-17B concentrations indicate ovulation within 48 h of parturition and then immediate resumption of follicular growth. Uterine histology and immunohistochemistry revealed progressive epithelial repair, endometrial growth and spiral artery assembly and remodelling in dams postpartum. Blastocysts were seen in the uterine lumen at day 4–5 postpartum and embryos had implanted superficially with minimal stromal invasion by day 5–6. This study provides further evidence for the unique, humanesque reproductive biology of spiny mice and for a postpartum ovulation using endocrine and morphological changes observed during early pregnancy. Taken together, our data suggest that spiny mice may act as appropriate models of human pregnancy disorders such as implantation failure or pre-eclampsia.